Outcome of Opsoclonus-Myoclonus Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Long-term neurologic sequelae and predictors for disease outcome were identified in 101 patients diagnosed with opsoclonus-myoclonus syndrome (OMS) over a 53-year period at Royal Hospital for Sick Children, Glasgow; Great Ormond Street Hospital, London; and Guy's and St Thomas Evelina Children's Hospital, London, UK.